2019
DOI: 10.1096/fj.201802264r
|View full text |Cite
|
Sign up to set email alerts
|

The NMR‐based characterization of the FTY720‐SET complex reveals an alternative mechanism for the attenuation of the inhibitory SET‐PP2A interaction

Abstract: The su(var)3‐9, enhancer of zeste, trithorax (SET)/inhibitor 2 of protein phosphatase 2A (PP2A) oncoprotein binds and inhibits PP2A, composed of various isoforms of scaffolding, regulatory, and catalytic subunits. Targeting SET with a sphingolipid analog drug fingolimod (FTY720) or ceramide leads to the reactivation of tumor suppressor PP2A. However, molecular details of the SET‐FTY720 or SET‐ceramide, and mechanism of FTY720‐dependent PP2A activation, remain unknown. Here, we report the first in solution exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 78 publications
(105 reference statements)
4
33
0
Order By: Relevance
“…Furthermore, our simulation results showed that the ceramide molecule adopts an "extended" conformation inside the SET protein, in which the sphingosine and lipid chains are placed in opposite directions. This finding was further confirmed by the NMR model suggested previously by De Palma et al [41]. The docking results of compound 1 revealed that the ligand exhibited a similar extended orientation and comparable binding interactions within the pocket (S = −6.6821 kcal/mol).…”
Section: In Silico Studiessupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, our simulation results showed that the ceramide molecule adopts an "extended" conformation inside the SET protein, in which the sphingosine and lipid chains are placed in opposite directions. This finding was further confirmed by the NMR model suggested previously by De Palma et al [41]. The docking results of compound 1 revealed that the ligand exhibited a similar extended orientation and comparable binding interactions within the pocket (S = −6.6821 kcal/mol).…”
Section: In Silico Studiessupporting
confidence: 86%
“…Additionally, along the N-terminal region, the 1,4-dihydroxy array of the dihydrosphingosine chain donates two H-bonds to Glu-111 (2.843 and 2.849 Å, respectively), while the 3-hydroxy group accepts an H-bond from Gln-65 with 2.138 Å ( Figure 6A). Previous data had indicated that the amino acid residues 36-124 of the N-terminal region are involved in the inhibition of PP2A as well as the binding with ceramide [41]. On the other hand, compound 2 was found to exhibit a different compact conformation within the active site, where the dihydrosphingosine backbone runs perpendicular to both the fatty acyl chain and the sugar moiety.…”
Section: In Silico Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In AML, SET is highly dependent on MYC-transcriptional activity and recruitment of RUNX1 and GATA2 on its promoter [102]. By impairing SET binding to PP2A, with molecules like FTY720 [82,105], CM-1231 [106], or OP449 [107,108] it is possible to re-establish PP2A activity, inhibiting tumor growth [91,109] and overcoming therapeutic resistance in preclinical models [92,108]. SET is known to interact with SETBP1 (SET-binding protein 1), which protects SET from protease cleavage.…”
Section: Arpp19mentioning
confidence: 99%